Infrared Thermography Procedure For Boundary Layer Transition Detection - Zaccara, M.; Campanardi, G.G.; Scavella, P.; Greco, C.S.; Cardone, G. (My University, 2024)
Laminar to turbulent transition detection and control is a crucial aspect when designing aerodynamic shapes and assess their qualities. Many unpredictable factors present in general fluid dynamics phenomena determine the uncertainty of its estimation. A large spread of experimental techniques has been developed, and ever finer methods are used to be more confident with transition prediction. Infrared Thermography is one of the more suitable techniques when dealing with requirements like non-intrusive testing. It provides spatially resolved measurement and also real-time analyses. In this work, many experiments are performed with Infrared Thermography to detect transition on a generic wing at several angles of attack by using a particular condition on the inflection point of the temperature profile in the chordwise direction.